1975
DOI: 10.1128/jb.123.1.336-345.1975
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructal morphology of some prokaryotic microorganisms associated with the hindgut of cockroaches

Abstract: Scanning electron microscopy and transmission electron microscopy have been used to visualize the morphology and ultrastructure of two types of microorganisms in the hindgut of the cockroach Blaberus posticus. Both organisms, designated as either short or long rods, are attached to chitinous projections from the gut wall. Micrographs suggest that the organisms are prokaryotic with a cell wall complex characteristic of gram-negative bacteria. However, certain differences were noted between the cell wall complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Phoresis, or the colonization by a microbe of the surface of another macro-or microorganism, is common in nature (2), and the attach-ment of organisms to gut epithelial tissues has been well documented for a variety of animal hosts (6,15,35,39,41,(46)(47)(48), including insects other than termites (21). The present findings extend the generality of this phenomenon since phoresis was apparent not only at the epithelial surface (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Phoresis, or the colonization by a microbe of the surface of another macro-or microorganism, is common in nature (2), and the attach-ment of organisms to gut epithelial tissues has been well documented for a variety of animal hosts (6,15,35,39,41,(46)(47)(48), including insects other than termites (21). The present findings extend the generality of this phenomenon since phoresis was apparent not only at the epithelial surface (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…It should be noted that these bacteria occur in sites removed from the food flow through the lumen of the proventriculus, which should help stabilize their residence there. Bacteria have been reported in the intestine of termites (Leidy 1881;Breznak & Pankratz 1977;Bignell et al 1980;Czolij et al 1985), cockroaches (Foglesong et al 1975;Bracke et al 1979), millipedes (Crawford et al 1983), and bees (Bailey 1963;Cruz-Landim 1972Clark 1977;Peng & Marston 1986;Gilliam et al 1988;Cruz-Landim & Moraes 1996).…”
Section: Discussionmentioning
confidence: 99%
“…For example, 13 morphotypes were found in the termite paunch and midgut (Breznak & Pankratz 1977), at least 27 morphotypes in the termite paunch (Czolij et al 1985), and filamentous and non-filamentous forms throughout the entire termite gut (Bignell et al 1980). Two types of microorganisms (gram-negative short and long rods) were reported in the cockroach hindgut (Foglesong et al 1975) and "a variety of bacteria in the colon" of the cockroach (Bracke et al 1979). "At least three bacterial morphotypes" were found in the hindgut of a desert millipede (Crawford et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Other relationships between insects and microbes have been demonstrated. For example, Foglesong et al (5) demonstrated that a variety of microorganisms are present in the hindguts of cockroaches. Barras (1) elucidated a symbiotic relationship between certain fungi and Southern pine beetles.…”
mentioning
confidence: 99%